The Literature Review of Tools and Methods for Evaluating Physical Activity Program at Workplace - Ni Made Hegard Sukmawati (Scopus ID: 57189732715) (Warmadewa University, 2020)
Background: workplace is an important setting for health promotion on physical activity programs. Establishing PA intervention in workplace is believed to give more substantial impact than in many other communities. However, the effectiveness of the physical activity intervention in occupational space has been questioned. Physical activity is a convoluted and varying behavior, and the ability to measure the association between physical activity and chronic diseases is strongly dependent on the validity of the tools. Objective: The goal of this study is to review the type of measurements, reliability and validity of instruments/methods of measuring occupational PA. Method: Relevant peer-reviewed journals were collected from two electronic database, Medline and PubMed, using advanced search strategy and eligibility criteria. Results: The searching strategy has generated 413 articles in total and the criteria have narrowed the result to 12 relevant articles. The BRFSS, the IPAQ-L, the MOSPA-Q, the OSPAQ and the OPAQ have been proven to have good reliability. However, these questionnaires showed poor to moderate criterion validity, thus objective measures of occupational PA, such as accelerator, is still the best option. Keywords: physical activity, workplace, occupational, validity, reliability